New Method of Synthesis and Biological Evaluation of Some Combretastatin A-4 Analogues - Malysheva, Yulia B.; Combes, Sebastien; Fedorov, Alexey Yu.; Knochel, Paul; Gavryushin, Andrei E. (Synlett, 2012)
A series of novel combretastatin A-4 analogues was synthesized in 36–64% yields by Negishi cross-coupling reaction under mild conditions. The prepared compounds exhibit good cytotoxicity against HBL100 epithelial cell lines (IC50 = 0.022–10.31 µМ).
Keywords: antitumor agents; cross-coupling; organometallic reagents; magnesium–zinc exchange; cytotoxicity